Development of the Nagari Tuo Pariangan Tourism Village: Potentials, Challenges, and Sustainable Strategies - Cicha Putri Aliva; Idea Alvira (Melayu Arts and Performance Journal, 2025)
This study examines the development of Nagari Tuo Pariangan as a tourism village by analyzing its tourism potential, development challenges, and sustainable development strategies. Recognized globally for its natural landscape, terraced rice fields, and Minangkabau cultural heritage, Pariangan possesses significant tourism assets that require structured and sustainable management. This research employs a qualitative descriptive approach based on a literature study, drawing on academic publications, policy documents, and previous research related to tourism village development and sustainable tourism. The findings indicate that the main challenges in developing Nagari Tuo Pariangan as a tourism village include limited infrastructure and accessibility, insufficient local human resource capacity, risks of cultural commodification, and unequal distribution of economic benefits. In response to these challenges, this study formulates a holistic development strategy encompassing improvements in accessibility and information and communication technology, continuous capacity-building programs for local communities, cultural preservation efforts, and the establishment of cooperative-based economic management to ensure fair benefit distribution. This study contributes to sustainable tourism discourse by offering an integrated development framework that can serve as a reference for tourism village management and future research.